ANALISIS PERBANDINGAN DAYA DUKUNG PONDASI TIANG PANCANG PADA TANAH LUNAK DENGAN METODE MANUAL DAN ELEMEN HINGGA SAP 2000 - Ngudi Hari Crista; Trias Widorini; Bambang Purnijanto (JITEK (Jurnal Ilmiah Teknosains), 2021)
Various types of concrete piles with dimensions of square, triangle, or circle are produced to be used as deep foundations. To get a solid superstructure, a foundation with a high bearing capacity is needed, the bearing capacity of the pile depends on local soil conditions, but if the soil is soft soil, an investigation is needed to determine the carrying capacity. The research was conducted to obtain the carrying capacity of the pile by means of manual calculations which will then be compared with calculations using SAP 2000 version 14. Soil data analyzed were sondir and boring data which were the results of the laboratory in the form of soft soil data which would be analyzed manually with took a sample of rectangular type piles with materials from K-600 concrete. From the research results obtained square stakes with dimensions of 20 x 20 cm which were analyzed with Sondir data, Boring data, and analysis based on SAP 2000 software, the relative carrying capacity values were the same, namely 13.18 tons and 13.31 tons, but for analysis using power software support the pile is higher with a value of 15.62 tons. At the dimensions of the stake 25 x 25 cm and 30 x 30 cm the value of the carrying capacity still tends to be the same as the value of 17.06 tons and 18.64 tons for the dimensions of 25 x 25 and the value of the carrying capacity of 21.17 tons and 24.76 tons from the analysis results. dimensions of 30 x 30 cm but there is already a difference in carrying capacity but relatively small, for the calculation of the software still produces a larger carrying capacity value, namely 22.24 tons and 29.95 tons, while for fishing rods with dimensions of 45 x45 cm, it has a pile bearing capacity, especially with analysis SAP 2000 software produces a relatively large carrying capacity value of 73.69 tons so that it can be concluded that the manual calculation to obtain the bearing capacity of the pile. The value is smaller than the calculation in the SAP 2000 software.